APPLYING DEONTOLOGICAL PRINCIPLES IN EFL DIGITAL COMMUNICATION - Sapayeva Zulayho Sherzodovna (TADQIQOTLAR, 2026)
Abstract This article examines the application of deontological principles in digital communication within English as a Foreign Language (EFL) education. The study is based on a qualitative analysis of existing academic literature related to digital communication, ethics, and language teaching. The findings reveal that deontological ethics, emphasizing moral duties such as honesty, respect, responsibility, and privacy, significantly contributes to the development of ethical digital communication culture among future teachers. The results indicate that integrating deontological principles enhances learners’ engagement, promotes responsible behavior, and strengthens professional competencies. The study concludes that deontological ethics serves as a strong methodological foundation for fostering ethical awareness and effective communication in digital EFL environments.